Bench Surgery for Urolithiasis in Renal Transplant: A Sensible Option!! - Abhiyutthan Singh Jadaon; Chandra Pal Singh (Indian Journal of Transplantation)
Introduction: Renal transplantation is the wisest option for patients with end-stage renal disease. Due to less availability of organs for transplantation, professionals are compelled to use organs from expanded-criteria donors. Urolithiasis in the to be transplanted kidney of donor is considered a relative contraindication due to the complications from stone in recipients like infection leading to sepsis, urinary tract obstruction, and also loss of allograft function. Therefore management of stones is needed, prior to transplanting that kidney. Material and Methods: A retrospective study was undertaken to identify those living renal donors who underwent ex vivo stone removal on the bench before transplantation. Results: In the time period of 2021 and 2023, we carried out 208 living donor Renal transplants at different centers in Rajasthan, Delhi & Haryana, INDIA. Of these, 32(18.2%) donor kidneys had to undergo ex vivo bench surgery for the removal of the stones. Discussion: In our study none of the grafts undergoing stone surgery showed evidence of stone recurrence at the follow-up examination. In all recipients those underwent bench URS had kidney graft survival was 96.8% after long-term follow-up. Conclusion: To date, there are no definitive criteria for the surgical management of urolithiasis from living donors. In this study we report our surgical experience and long-term follow-up in a series of living kidney donors (LKD) with asymptomatic kidney stones, after ex vivo ureterorenoscopy (URS) for stone removal before kidney transplantation.